The experience of breast pain (mastalgia) in female runners of the 2012 London Marathon and its effect on exercise behaviour - Brown, N.; White, J.; Brasher, A.; Scurr, J. (British Journal of Sports Medicine, 2014)
Background: For female marathon runners, breast pain (mastalgia) may be an important issue which has yet to be considered. This study aimed to determine the prevalence and severity of mastalgia in female marathon runners, identify factors that increase mastalgia and methods used to overcome mastalgia, and explore the impact that mastalgia may have on marathon training.